Assessment of radon emanation rate from various building materials in Malaysia using tight chamber method / Siti Fatimah Saipuddin and Ahmad Saat - Saipuddin, Siti Fatimah; Saat, Ahmad (2018)
Radon gas has been known as one of the main factors that cause breathing complications which lead to lung cancer, second only after smoking habit. As one of the most commonly found Naturally Occurring Radioactive Materials (NORM), its contribution to background radiation is immense, and its contributors, Uranium and Thorium are widely available on Earth and have been in existence for such a long time with long half-lives. Indoor radon exposure contributed by building materials worsens the effects. The probability of inhaling radon-polluted air and being surrounded by it in any buildings is very high. This research is focused on the detection of radon emanation rate from various building materials which are commonly being used in Malaysia. Throughout this research, common building materials used in constructions in Malaysia were collected and indoor radon exposure from each material was measured individually using Tight Chamber Method coupled to a Continuous Radon Monitor, CRM 1029. It has been shown that sand brick is the biggest contributor to indoor radon compared to other samples such as sand, soil, black cement, white cement, and clay brick. From the results, materials which have high radon emanation could be reconsidered as building materials and mitigation action can be chosen, suitable to its application.